Causal Relationship between Electric Consumption and Economic Growth in South East Sulawesi - Rahim, Manat; Adam, Pasrun; Suriadi, La Ode; Saenong, Zainuddin; Atmodjo, Ery; Rumbia, Wali Aya; Tamburaka, Irma P. (International Journal of Energy Economics and Policy, 2018)
This study aims to investigate the causal relationship between electric consumption and economic growth in Southeast Sulawesi. Time series of electric consumption and per capita regional gross domestic product data in the period of 1985 to 2016 were used in this study. The causal relationship were examined using an autoregressive distributed lag (ARDL) model and Granger causality test. The tests revealed a strong positive causal relationship between electric consumption and economic growth of Souetheast Sulawesi in the long-run. Each 1% increase in electric consumption would caused 0,31% increase in economic growth. In the short-run, however, weak relationship exists between electric consumption and economic growth. Hence, electric consumption contributes to economic growth of Southeast Sulawesi in the long-run and in the short-run. Keywords: Electric consumption, economic growth, ARDL model, Granger causality. JEL Classifications: C120, C320, E2, E210. https://doi.org/10.32479/ijeep.6973